Do Self-Reported Traits and Aggregated States Capture the Same Thing? A Nomological Perspective on Trait-State Homomorphy. Issue 5 (July 2019) - Rauthmann, John F.; Horstmann, Kai T.; Sherman, Ryne A.
Convergent correlations between traits and state aggregates from experience sampling cannot fully establish trait-state homomorphy (the extent to which the same constructs are measured). With a nomological vector correlation and lens model approach, we test how similar nomological networks of traits and state aggregates are to each other: A trait and state-aggregate capture the same construct when both show highly similar nomological associations to a common set of correlates. In large experience sampling ( N = 209) and life-logging studies ( N = 298), Extraversion, Conscientiousness, and Agreeableness tended to show more and Openness, Honesty/Humility, and Neuroticism/Emotionality tended to show less trait-state homomorphy. However, these general findings differed somewhat at the aspect level, with Neuroticism and Extraversion aspects tending to show more versus Openness and Honesty/Humility aspects tending to show less homomorphy. The proposed nomological approaches can be flexibly applied to other traits, states, and correlates.